Perubahan kuat tekan pasta dan beton dengan fly ash oleh pengaruh moist dan steam curing - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT The use of Fly ash as admixture in concrete has become common practice in both the precast and cast -in-place concrete. For the precast concrete with steam curing method, the use of Fly ash still requires further investigation regarding the micro structural changes in concrete that directly affects the mechanical characteristics of the concrete. In this study, the specimen tested were in the form of cement paste and concrete, the percentage of Fly ash in the concrete ranges between 0% to 25%. The post-mixing treatment of the specimen were with the moist curing and the steam curing process in variable temperature of 60 °C, 70 °C and 80 °C. The micros structural changes to be analysed were mainly focused on the following aspects : the changes of Crystal arrangement with X-Ray Diffractometer. the changes of pore diameter and pore shape when observed with Scanning Electron Microscope, and the development, of compressive strengths of the specimen. The results of strength test in this study show that the stream curing process of 80"C causes the highest initial compressive strengths. However at the end of 91-day test period the highest compressive strengths are achieved by the specimen subjected with stream curing process of 70°C. This evidence is supported by the results from observations with the X-Ray Diffractonieter and with the Scanning Electron Microscope. Those observations several that formation of crystal arrangement in the material is somewhat less perfect when the curing temperature is 80"C or higher. In additional, it is also found from the mercury-porosity analyses that the use of Fly ash in mixture tends to cause formation of smaller pore diameters in concrete, and this also means formation of stronger concrete